Morus alba L. Leaves – Integration of Their Transcriptome and Metabolomics Dataset: Investigating Potential Genes Involved in Flavonoid Biosynthesis at Different Harvest Times - Xu, Ding-Qiao; Cheng, Shu-Yan; Zhang, Jun-Qing; Lin, Han-Feng; Chen, Yan-Yan; Yue, Shi-Jun; Tian, Meng; Tang, Yu-Ping; Zhao, Yu-Cheng (Frontiers in Plant Science, 2021)
The Mulberry (Morus alba L.) leaf is a classic herb commonly used in traditional Chinese medicine. It has also been used as animal feed for livestock and its fruits have been made into a variety of food products. Traditionally, mulberry leaf harvesting after frost is thought to have better medicinal properties, but the underlying mechanism remains largely unsolved. To elucidate the biological basis of mulberry leaves after frost, we first explored the content changes of various compounds in mulberry leaves at different harvest times. Significant enrichment of flavonoids was observed with a total of 224 differential metabolites after frost. Subsequently, we analyzed the transcriptomic data of mulberry leaves collected at different harvest times and successfully annotated 22,939 unigenes containing 1,695 new genes. KEGG analysis revealed 26, 20, and 59 unigenes related to flavonoids synthesis in three different groups harvested at different times. We found that the expression levels of flavonoid biosynthesis-related unigenes also increased when harvested at delayed time, which was consistent with the flavonoid accumulation discovered by the metabolomic analysis. The results indicated that low temperature may be a key trigger in flavonoid biosynthesis of mulberry leaves by increasing the expression of flavonoid biosynthesis-related genes. This study also provides a theoretical basis for the optimal harvest time of mulberry leaves.